HIKMAT SEBAGAI FONDASI PENDIDIKAN KRISTIANI: MEREFLEKSI 1 RAJA- RAJA 3:1-15 - Cindi Cenora; Damaris Daturara’, Arkino Marson, Marlina Limbong Sombo Datu, Juniaty Bine’ Rombe (HUMANITIS: Jurnal Homaniora, Sosial dan Bisnis, 2023)
This research aims to examine the concept of wisdom in the context of Christian education using the narrative of wisdom bestowed upon King Solomon in 1 Kings 3:1-15 as a starting point. The study integrates an exegesis of the Biblical text, analysis of Christian literature, and an educational approach to grasp the profound meaning of wisdom and how it can serve as a crucial foundation in Christian education. The findings of this research indicate that wisdom, as reflected in the story of Solomon, encompasses not only wisdom or knowledge, but also includes moral, ethical, and spiritual aspects. Wisdom in Christian education goes beyond acquiring knowledge; it also involves the formation of strong character and spirituality. This research also highlights the importance of integrating the teachings of wisdom into the Christian education curriculum, providing guidance for teachers to develop teaching strategies that emphasize the values of wisdom, and exploring the potential for personal development within the context of Christian education. Therefore, this research contributes to a deeper understanding of the role of wisdom as the foundation of Christian education, offering both theoretical and practical foundations for the development of a holistic Christian education based on the wisdom values of the Bible.